JEJAK-JEJAK PLURALISME AGAMA DALAM SUFISME - Hamdie, Ilham Masykuri (UIN Antasari Banjarmasin, 2019)
This article intends to explore Sufism about the pluralism of religion. Khazanah Sufism is known synonymous with the esoteric approach in religion. Through this esoteric approach, the unity of religions or pluralism is very likely to be achieved, because all religions ultimately meet God. In Islam this aspect of esotericism is known to be discussed by Sufism or Sufi figures who have many concepts of unity (al-wahdat) such as Wahdat al-Wujud, Wahdat al-Syuhud, Wahdat al-Ummah and Wahdat al-Adyan. This article is the result of library research that raises the issue of Sufi treasures around religious pluralism. The study in this paper can be considered important, theoretically besides being able to enrich the treasury of Islamic thought more specifically in the field of Sufism, it can also strengthen the theological basis for understanding pluralism of religion, which at the level of praxis can encourage a more harmonious relationship between and among adherents of religion that different. Moreover, if so far the discourse on religious pluralism is considered to always refer to the works of Western religious scholars, those who define pluralism as the view that the One manifests to many or that particular religions are a response to the Almighty, in fact some Sufism or Sufi figures actually have long, first discuss it philosophically and deeply.